Molecular Analysis And Protein Quantification Of Rh Blood Group System Among Blood Donors At The National Blood Centre, Malaysia - Musa, Rozi Hanisa (2014)
Rh is the most polymorphic and immunogenic human blood group system, with over 50 antigens now identified. The Rh antigens are located on two proteins, RhD and RhCE: the former carries the D antigen, whilst the latter carries the C, c, E and e antigens. These antigens can be further subdivided into various genotypes. Rh adalah sistem kumpulan darah manusia yang paling polimorfik dan imunogenik, dengan lebih 50 antigen kini dikenal pasti. Antigen Rh terletak di atas dua protein, RhD dan RhCE: yang pertama membawa antigen D, manakala yang kedua membawa antigen C, c, E dan e. Antigen-antigen ini boleh dibahagikan lagi kepada pelbagai genotip.